Employment As Construction Manager: Construction Company Perception on Fresh Graduates - Disen, Ferderick Maldini anak; Omar, Roshartini; Kai Chen, Goh (Research in Management of Technology and Business, 2022)
Construction manager is a career in the construction industry that coordinate and supervise construction projects which is a tough approach for fresh graduates due to the tough competition in Malaysia. The objective of this study is to determine the requirement of fresh graduates to be employed as construction manager and to study the perception of construction industry on fresh graduates, and lastly to identify the improvement of university education system in preparing fresh graduates for employment in Kuching, Sarawak. This study adopts quantitative method to collect data by survey through Google form. The respondents are construction managers in Kuching, Sarawak. There are 82 responses collected out of 150 respondents have been approached which have responses rate of 55%. The data collected were analyzed using descriptive analysis method through Statistical Package for the Social Sciences (SPSS) version 26. The results reveal that possessing a construction bachelor’s degree, working experience, analytical thinking, organizational abilities, budget management, great effort in learning and industrious, and conflict management skills are required. Fresh graduates are perceived as reliable and capable performers by employers but lack required work experience and lack confidence in their skills. The Malaysian Higher Education can be improved by providing innovative infrastructure and technology, introducing real-world projects to students, and offering work experience to students as an outreach to local businesses.